A randomised clinical trial of comprehensive cardiac rehabilitation versus usual care for patients treated for infective endocarditis—the CopenHeartIE trial protocol. Issue 6 (21st November 2012) - Rasmussen, Trine Bernholdt; Zwisler, Ann-Dorthe; Sibilitz, Kirstine Lærum; Risom, Signe Stelling; Bundgaard, Henning; Gluud, Christian; Moons, Philip; Winkel, Per; Thygesen, Lau Caspar; Hansen, Jane Lindschou; Norekvål, Tone Merete; Berg, Selina Kikkenborg; et al.
Abstract : Introduction: Infective endocarditis (IE) is among the most serious infectious diseases in the western world. Treatment requires lengthy hospitalisation, high-dosage antibiotic therapy and possible valve replacement surgery. Despite advances in treatment, the 1-year mortality remains at 20–40%. Studies indicate that patients experience persisting physical symptoms, diminished quality of life and difficulties returning to work up to a year postdischarge. No studies investigating the effects of rehabilitation have been published. We present the rationale and design of the CopenHeartIE trial, which investigates the effect of comprehensive cardiac rehabilitation versus usual care for patients treated for IE. Methods and analysis: We will conduct a randomised clinical trial to investigate the effects of comprehensive cardiac rehabilitation versus usual care on the physical and psychosocial functioning of patients treated for IE. The trial is a multicentre, parallel design trial with 1 : 1 individual randomisation to either the intervention or control group. The intervention consists of five psychoeducational consultations provided by specialised nurses and a 12-week exercise training programme. The primary outcome is mental health (MH) measured by the standardised Short Form 36 (SF-36). The secondary outcome is peak oxygen uptake measured by the bicycle ergospirometry test. Furthermore, a number of exploratory analyses will be performed. Based on sample size calculation, 150 patients treated for left-sided (native or prosthetic valve) or cardiac device endocarditis will be included in the trial. A qualitative and a survey-based complementary study will be undertaken, to investigate postdischarge experiences of the patients. A qualitative postintervention study will explore rehabilitation participation experiences. Ethics and dissemination: The study complies with the Declaration of Helsinki and was approved by the regional research ethics committee (no H-1-2011-129) and the Danish Data Protection Agency (no 2007-58-0015). Study findings will be disseminated widely through peer-reviewed publications and conference presentations. Registration: Clinicaltrials.gov identifier: NCT01512615 .